THE PROCESS OF WORKING WITH INFORMATION IS THE CONTENT OF IMPROVING STUDENTS’ COMPETENCE - Saidova Mohinur Jonpo`latovna; Elova Marjona Shomurod qizi (Galaxy International Interdisciplinary Research Journal, 2024)
As a result of socio-economic changes in our country, the need and task of modernizing many social institutions and, first of all, reforming the education system has arisen. As stated in the National Curriculum of General Secondary Education aimed at the development and regulation of the educational system, mathematics has been identified as one of the priority directions of the development of science in our country in 2020 and to bring the development of mathematics science and education to a new qualitative level a number of systematic works are being carried out.We all know that mathematics sharpens the human mind, develops focus, develops determination and will to achieve the desired goal, teaches discipline in an algorithmic way, and most importantly,encourages reflection and expands thinking.Honorable President Sh.M. As Mirziyoyev noted, "Mathematics is the basis of all sciences. A child who knows this subject well will grow up to be smart, broad-minded, and work successfully in any field" [4]. In these areas, new, modern electronic textbooks for students are being created and published based on the requirements of the times. The variety of the Mathematics textbook, published in 2021, and the cognitive and creative nature of the tasks are of special importance."We are the representatives of the enlightened people who consider the teacher as great as a father and always honor him. When I think of a teacher, I think of intelligent and modern, sincere and kind people who are the most dear and respectful to me. Because this teacher gave lessons and education to all of us and raised us among our loving parents. Today, we are creating the foundations of a new era of development of Uzbekistan. In this, our closest assistants are teachers and trainers, scientific and creative intellectuals. If the method of teaching in the school does not change, the quality, content, and atmosphere of education will not change," says ShavkatMirziyoyev [6]. In this regard, the experience of Finland was given as an example. This country is one of the most advanced in the world in general literacy, science and mathematics.